Dilemas e desafios da Universidade: Recomposição social e expectativas dos estudantes na Universidade de Coimbra - Elísio Estanque; João Arriscado Nunes (Revista Crítica de Ciências Sociais, 2003)
In the last decades, the system of higher education in Portugal has gone through profound changes, which are largely related to the democratization of access to the university. With the rapid expansion and the increasing strength of the market, higher education has revealed new contradictions and now faces new challenges. Drawing on the results of a survey of University of Coimbra students, the authors seek to analyze and discuss the ongoing changes at the level of student expectations and representations and their repercussions in the redefinition of the university’s mission. Dilemmes et défis de l’université : Recomposition sociale et attentes des étudiants à l’Université de Coimbra